TRPV1 receptors contribute to paclitaxel-induced c-Fos expression in spinal cord dorsal horn neurons - Kalynovska, N; Adamek, P; Palecek, J (Physiological research, 2017)
Transient receptor potential vanilloid type 1 (TRPV1) receptors are important in the development of different pathological chronic pain states. Here we examined the role of spinal cord TRPV1 receptors in the mechanisms leading to activation of dorsal horn neurons after paclitaxel (PAC) treatment. PAC is a widely used chemotherapeutic drug that often leads to development of painful neuropathy. Immunohistochemical analysis of c-Fos protein expression in dorsal horn neurons was used as a marker of neuronal activation. Rat spinal cord slices were processed for in vitro incubation with PAC (100 nM) and TRPV1 receptor antagonists (SB366791 and AMG9810; 10 microM). PAC treatment induced significant upregulation of c-Fos nuclear expression in superficial dorsal horn neurons that was diminished by TRPV1 receptor antagonists pre-incubation. These results further substantiated the role of spinal TRPV1 receptors in the development of paclitaxel-induced neuropathic pain and contribute to better understanding of the pathological mechanisms involved.
Keywords: buňky zadních rohů míšních; protoonkogenní proteiny c-fos; paclitaxel; Rats; Posterior Horn Cells; TRPV Cation Channels; Proto-Oncogene Proteins c-fos; Rats, Wistar; mužské pohlaví; fytogenní protinádorové látky; krysa rodu Rattus; Spinal Cord Dorsal Horn; Gene Expression; zvířata; kationtové kanály TRPV; exprese genu; Antineoplastic Agents, Phytogenic; potkani Wistar; Paclitaxel; zadní rohy míšní; Male; Animals